2003
DOI: 10.1016/s0277-9536(02)00131-4
|View full text |Cite
|
Sign up to set email alerts
|

Subjective social status: its determinants and its association with measures of ill-health in the Whitehall II study

Abstract: The purpose of this study was twofold-(1) investigate the role of subjective social status as a predictor of ill-health, with a further exploration of the extent to which this relationship could be accounted for by conventional measures of socioeconomic position; (2) examine the determinants of a relatively new measure of subjective social status used in this study. A 10 rung self-anchoring scale was used to measure subjective social status in the Whitehall II study, a prospective cohort study of London-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

46
801
4
19

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 850 publications
(892 citation statements)
references
References 32 publications
46
801
4
19
Order By: Relevance
“…A priority for future research should be the longitudinal analysis of the associations examined here so that causality can be established. Secondly, although there is convincing evidence that SSS is not a product of psychological bias Hu et al, 2005;Operario et al, 2004;Singh-Manoux et al, 2003), future research could add to this line of research by testing the associations between SSS and health against potential confounders such as negative affectivity. Further, an examination of the role of gender in the associations of SSS with health outcomes is warranted given the gender differences this study has identified.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A priority for future research should be the longitudinal analysis of the associations examined here so that causality can be established. Secondly, although there is convincing evidence that SSS is not a product of psychological bias Hu et al, 2005;Operario et al, 2004;Singh-Manoux et al, 2003), future research could add to this line of research by testing the associations between SSS and health against potential confounders such as negative affectivity. Further, an examination of the role of gender in the associations of SSS with health outcomes is warranted given the gender differences this study has identified.…”
Section: Discussionmentioning
confidence: 99%
“…Also, there is evidence that SSS relates to adolescent health (Goodman, Adler, Daniels, Morrison, Slap, & Dolan, 2003;Goodman, Adler, Kawachi, Frazier, Huang, & Colditz, 2001). In contrast, research has shown that SSS is not related at all to body mass index, sleep quality, and resting systolic blood pressure in women , angina and respiratory illness in women (Singh-Manoux et al, 2003), and difficulties in Activities of Daily Living (Hu et al, 2005). Also, studies have shown that adjusting for objective indicators of SES attenuates the associations of SSS with perceptions of physical health (Franzini & Fernandez-Esquer, 2006), diabetes, self-rated health, and depression in both sexes, and angina and respiratory illness in men (Singh-Manoux et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using validated standardized scales at baseline, we collected data on patient sociodemographic characteristics, SDH (including Medical Outcomes Study [MOS] survey 25 and subjective social status 26 30 ), and health care utilization. 22 …”
Section: Study Data and Outcome Measuresmentioning
confidence: 99%
“…Subjective social status has been related to a range of health-related factors such as self-rated health, heart rate and body fat distribution (9) , and reflects the cognitive averaging of standard markers of socio-economic position rather than psychological biases (22) . Previous studies have established a link between SES and diet.…”
Section: Socio-economic Statusmentioning
confidence: 99%